2009
DOI: 10.1063/1.3226560
|View full text |Cite
|
Sign up to set email alerts
|

Symmetries and alignment of biaxial nematic liquid crystals

Abstract: The possible symmetries of the biaxial nematic phase are examined against the implications of the presently available experimental results. Contrary to the widespread notion that biaxial nematics have orthorhombic symmetry, our study shows that a monoclinic (C(2h)) symmetry is more likely to be the case for the recently observed phase biaxiality in thermotropic bent-core and calamitic-tetrapode nematic systems. The methodology for differentiating between the possible symmetries of the biaxial nematic phase by … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 70 publications
(107 reference statements)
0
36
0
Order By: Relevance
“…These two tensor order parameters Q and B, however, are generally insufficient for the description of a biaxial phase with the orthorhombic symmetry (D 2h ) as shown by Gorkunov et al 5 In principle a low symmetry biaxial nematic phase with C 2h symmetry may also exist. 12 The absorbance profile vs. the angle of polarization of the IR beam can in principle give a direct evidence of departure from the orthorhombic symmetry. Lower symmetry shall break the overall symmetry of the absorbance profile as shown.…”
Section: Polarized Infrared Spectroscopymentioning
confidence: 99%
“…These two tensor order parameters Q and B, however, are generally insufficient for the description of a biaxial phase with the orthorhombic symmetry (D 2h ) as shown by Gorkunov et al 5 In principle a low symmetry biaxial nematic phase with C 2h symmetry may also exist. 12 The absorbance profile vs. the angle of polarization of the IR beam can in principle give a direct evidence of departure from the orthorhombic symmetry. Lower symmetry shall break the overall symmetry of the absorbance profile as shown.…”
Section: Polarized Infrared Spectroscopymentioning
confidence: 99%
“…For example, it has long been appreciated that there should be more than one type of biaxial nematic each with a different point group symmetry. Recently, however, it has been shown how NMR spectroscopy might be used to distinguish between biaxial nematic phases with different point group symmetries; in particular those with D 2h and C 2h symmetries [1].…”
Section: Introductionmentioning
confidence: 99%
“…In view of the subtleties in the differences between non-polar biaxial nematics with C 2h and D 2h symmetries as well as C i the identification of these new biaxial nematics promises to present even greater problems [1]. To help in this challenging task we have developed a molecular field theory for the phases, isotropic, uniaxial nematic, biaxial nematic both D 2h and C 2h formed by molecules with C 2h…”
Section: Introductionmentioning
confidence: 99%
“…The situation is, however, different for the presently available observations of biaxial orientational order in thermotropic nematics. As detailed in ref (20), the experimental results involving measurements on aligned samples, although routinely analysed assuming a D 2h symmetry, do not particularly support this symmetry and in some cases appear to contradict it. Thus, the NMR measurements on bent-core nematics (9) using deutriated probe solutes indicate the presence of biaxial order but are not detailed enough to single out a particular symmetry for the observed phase biaxiality.…”
Section: The Symmetries Of the Biaxial Nematic Phasementioning
confidence: 95%
“…Thus, the NMR measurements on bent-core nematics (9) using deutriated probe solutes indicate the presence of biaxial order but are not detailed enough to single out a particular symmetry for the observed phase biaxiality. On the other hand, the biaxial order in calamitic tetramer nematics, reported first from IR spectroscopy studies on aligned samples (10) and subsequently confirmed by NMR measurements using deuteriated probe solutes (21), when analyzed on the assumption of D 2h symmetry leads to inconsistently large values of biaxial order parameters and to mutually conflicting inferences regarding the molecular attributes underlying phase biaxiality (20). In addition to these difficulties, X-ray diffraction studies in the nematic phase of bentcore compounds (22)(23), as well as in the nematic phase of the side-on monomers which form the calamitic tetramer compounds (24)(25), show the presence of local biaxial order that is characteristic of tilted-layer domain structures, thus favouring a monoclinic rather than orthorhombic symmetry for the biaxial phase that is formed when these domain structures become macroscopically ordered in the transverse direction (17).…”
Section: The Symmetries Of the Biaxial Nematic Phasementioning
confidence: 99%